PENGARUH TABUNGAN WADIAH DAN GIRO WADIAH TERHADAP LABA BERSIH PADA BANK BJB SYARIAH PERIODE 2020-2022 - Sholawati, Yuaffa; Suharto, Toto (Institut Agama Islam Negeri Kerinci, 2024)
ABSTRACT This research was conducted to determine whether or not there is an effect of wadiah savings and wadiah demand deposits on net income at Bank BJB Syariah for the period 2020 - 2022. The type of research used in this study using quantitative research with secondary data and purposive sampling techniques. In this study, the sample data used was 36 months, the data were wadiah savings, wadiah current accounts and net profit of BJB Syariah bank for the period 2020 - 2022 which were sourced from the financial statement data of BJB Syariah bank. The data analysis technique used in this research is descriptive statistical test, classical assumption test, multiple linear regression test, determination coefficient test and hypothesis testing using SPSS Version 25. The results of this study indicate that the wadiah savings variable has a positive and significant effect on net profit with a positive regression coefficient value of 0.231. However, the wadiah current account variable has a negative and insignificant effect on net profit with a negative regression coefficient value of -0.231. negative regression coefficient value of -0.070. While there is positive and significant effect of the independent variable or both independent variables on net profit with a regression coefficient value of -0.070. independent variables on net income with a coefficient of determination of 0.761. ABSTRAK Penelitian ini dilakukan untuk mengetahui ada atau tidaknya pengaruh tabungan wadiah dan giro wadiah terhadap laba bersih pada Bank BJB Syariah periode 2020 – 2022. Jenis penelitian yang digunakan pada penelitian ini dengan menggunakan penelitian kuantitatif dengan data sekunder dan teknik pengambilan sampling secara purposive sampling. Dalam penelitian ini sampel data yang digunakan sebanyak 36 bulan, data tersebut yaitu tabungan wadiah, giro wadiah dan laba bersih bank BJB Syariah periode 2020 – 2022 yang bersumber dari data laporan keuangan bank BJB Syariah. Teknik analisis data yang digunakan penelitian ini adalah uji statistik deskriptif, uji asumsi klasik, uji regresi linear berganda, uji koefisien determinasi dan uji hipotesis dengan menggunakan SPSS Versi 25. Hasil dari penelitian ini menunjukan bahwa variabel tabungan wadiah berpengaruh positif dan signifikan terhadap laba bersih dengan nilai koefisien regresi bertanda positif sebesar 0,231. Namun pada variabel giro wadiah berpengaruh negatif dan tidak signifikan terhadap laba bersih dengan nilai koefisien regresi bertanda negatif sebesar -0,070. Sementara terdapat pengaruh positif dan signifikan dari variabel independen atau kedua variabel bebas terhadap laba bersih dengan nilai koefisien determinasi sebesar 0,761.